Virtue's Pour: Exemplarity and Conversion in Thomas Heywood's The Fair Maid of the West, Part One - Zajac, Jordan (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2025)
In her theory of moral exemplarity, philosopher Linda Trinkaus Zagzebski observes how every era and culture has recognized supremely good individuals, models who inspire admiration and imitation. On the early modern stage, Bess Bridges — heroine of Thomas Heywood’s The Fair Maid of the West — emerges as one such magnanimous figure. Her virtuous exemplarity enkindles deep admiration in other characters, their mimetic responses leading to metanoia. This essay explores the moral psychology of admiration in Heywood’s play, the complex relationship between the passions and conversion, and early modern theatre as a school and fruitful site for the realization of virtue.